[Translated article] Characteristics, Management, and Prognostic Implications of Adverse Effects of Immune Checkpoint Inhibitors: A Systematic Review - G. Juan-Carpena; J.C. Palazón-Cabanes; M. Blanes-Martínez (Elsevier, 2022)
Immune checkpoint inhibitors (ICIs) have significantly advanced the treatment of cancer. They are not, however, free of adverse effects. These effects are called immune-related adverse events (irAEs) and often involve the skin. Most of the information on cutaneous irAEs comes from clinical practice. We therefore conducted a thorough review of the characteristics of cutaneous irAEs, recommendations for treatment, and their association with prognosis. The most common events are exanthema, pruritus, vitiligo, and hair loss, although ICIs can cause a wide range of cutaneous dermatoses. The reported association observed between certain reactions and a favorable response to cancer treatment should be interpreted with caution. Dermatologists should be involved in the multidisciplinary care of patients being treated with ICIs as they have an essential role in the diagnosis and treatment of cutaneous irAEs. Resumen: Los fármacos inhibidores de los puntos de control inmunitario han supuesto un importante avance en el tratamiento oncológico. Sin embargo, su uso no está exento de reacciones no deseadas, denominadas efectos adversos inmunorrelacionados, siendo los cutáneos particularmente frecuentes. El conocimiento que tenemos sobre los efectos adversos inmunorrelacionados cutáneos procede fundamentalmente de la práctica clínica. Por lo tanto, en este trabajo se revisan en detalle sus características, así como las recomendaciones sobre su tratamiento y sus implicaciones pronósticas. Los más frecuentes son el exantema, el prurito, el vitíligo y la alopecia; sin embargo, estos fármacos pueden producir una amplia variedad de dermatosis. La asociación observada entre ciertos tipos de reacciones cutáneas con una respuesta oncológica favorable al tratamiento debe interpretarse con cautela. El dermatólogo ha de participar en el cuidado multidisciplinar de estos pacientes, pues desempeña un papel fundamental en el diagnóstico y el tratamiento de estas reacciones cutáneas adversas.